Electoral abstention in a time of economic crisis in Greece - Panagiotis Artelaris; Anastasis Katsinis; Yannis Tsirbas (Journal of Maps)
Between 2009 and 2015, Greece faced one of the most severe economic downturns experienced by any European country in the last century. This challenging period was not only marked by significant economic decline but also by political uncertainty and significant shifts in the country's electoral landscape. The aim of the paper is to identify the recent changes in electoral abstention rates in Greece providing a detailed analysis at the local (i.e. the municipal) level. This study utilizes cartographic visualizations based on the parliamentary elections held between of 2009 and 2019. By addressing a topic that has been largely overlooked, this research seeks to contribute fresh and valuable insights into a period characterized by a severe economic shock.